2006
DOI: 10.1111/j.1537-2995.2006.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of selected viral infections among blood donors deferred for potential risk to blood safety

Abstract: Blood donors deferred for standard blood donor questions regarding risk of viral hepatitis as well as those with a history of intravenous drug use were more likely to have higher hepatitis marker rates than those who were not deferred. No significant findings were identified for other markers or questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
1
26
1
Order By: Relevance
“…This rate was similar to comparable studies: In the literature, about 10-15% of applicant donors are deferred due to the DQ [4][5][6]. Still, in comparison to the established DQ, we found an increase in deferrals by 5.4% and 1.4% in first-time and repeat donations respectively.…”
Section: Discussionsupporting
confidence: 75%
“…This rate was similar to comparable studies: In the literature, about 10-15% of applicant donors are deferred due to the DQ [4][5][6]. Still, in comparison to the established DQ, we found an increase in deferrals by 5.4% and 1.4% in first-time and repeat donations respectively.…”
Section: Discussionsupporting
confidence: 75%
“…Instead, additional information and education is needed, like in other health‐related disciplines. Such a questionnaire should be updated regularly as questionnaires evaluated periodically have shown to significantly reduce the prevalence of HIV and HCV 35 …”
Section: Discussionmentioning
confidence: 99%
“…Ideally, there should be an acceptable balance between the costs and impact of preventive measures taken on the one hand, versus the savings and advantages of these measures on the other hand. In the case of the DHQ this balance has not been well studied 9‐13. TTI screening activities were recently reviewed by O'Brien and colleagues .…”
Section: Tti Statistics In the Netherlands1‐5mentioning
confidence: 99%
“…Goldman and coworkers studied the use of the DHQ, examining optimal wordings, formats, and lengths of questions and found room for improvement on these topics. Zou and coworkers studied the prevalence of TTIs in deferred donors. This study, with a 13% enrolment, showed odds ratios of 3.4 to 18.1 for the prevalence of TTIs in donors deferred for high TTI risk such as intravenous (IV) drug use.…”
Section: Tti Statistics In the Netherlands1‐5mentioning
confidence: 99%